Karakteristik backpacker nusantara dalam komunitas “backpacker international” - Susanti, Luh Eka; Supartini , Ni Luh; Semara, I Made Trisna (Jurnal Ilmiah Hospitality Management, 2022)
In society’s perception, backpackers are generally travelers who choose to travel for long periods of time, at low costs using public transportation and relatively cheap accommodation. Usually, backpackers come from the lower middle class because they want to travel that is cost-effective but rich in experience. In addition, most of these backpackers are students / students with an age range between 25 - 35 years. Over time and an era that has changed the human mindset, a significant shift has begun to occur, especially for the tourist actor himself as a backpacker. Although the above characteristics are still a strong concept for a backpacker, there are a number of things that are starting to shift. Some of these things are 1) backpackers do not always come from the lower middle class, and 2) a shift in the age of the backpacker criteria (tourists over 35 years old choose to be backpackers). Therefore, it is interesting to study from this phenomenon is the shift in people's perceptions of a backpacker where now backpackers also come from the upper middle class and have an age above 35 years. The data is taken from 35 backpackers who are members of the “Backpacker International” community, which consists of Indonesian backpackers whose travel destinations are to other countries (mostly in Europe). This research is an ethnographic study with a qualitative descriptive approach.